Diagnostics of atherosclerosis: Overview of the existing methods - Poznyak, Anastasia V.; Sukhorukov, Vasily N.; Eremin, Ilya I.; Nadelyaeva, Irina I.; Orekhov, Alexander N. (Frontiers in Cardiovascular Medicine, 2023)
Atherosclerosis was and remains an extremely common and serious health problem. Since the elderly are most at risk of cardiovascular risk, and the average life expectancy is increasing, the spread of atherosclerosis and its consequences increases as well. One of the features of atherosclerosis is its asymptomaticity. This factor makes it difficult to make a timely diagnosis. This entails the lack of timely treatment and even prevention. To date, in the arsenal of physicians, there is only a limited set of methods to suspect and fully diagnose atherosclerosis. In this review, we have tried to briefly describe the most common and effective methods for diagnosing atherosclerosis.